(untitled) (AL MUNAZHZHARAH, 2019)
In case ruling No.1566 / Pdt.G / 2017 / PA.Kab.Kdr is a joint property case after divorce. However, in his trial the defendant filed a counter-lawsuit or also called a reconciliation lawsuit to claim his rights which were still owed or unpaid namely to provide compensation for finalizing the house and shop, the child’s livelihood and the cost of obtaining a land certificate. However, in the reconvention lawsuit filed, it was stated by the judge that it could not be accepted because the case was obscuur libel.